2023
DOI: 10.1111/1471-0528.17392
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a maternal health medicines pipeline database 2000–2021: New candidates for the prevention and treatment of fetal growth restriction

Abstract: Objective The Accelerating Innovation for Mothers project established a new database of candidate medicines under development between 2000 and 2021 for five pregnancy‐related conditions, including fetal growth restriction. The objective was to assess medicines for fetal growth restriction and their potential for clinical use globally. Design Landscape analysis. Setting Global (focus on low‐ and middle‐income countries, LMICs). Sample Drugs, dietary supplements and biologics under investigation for prevention o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…So far, there is no effective treatment available for placenta‐mediated FGR, which is an active field for clinical research. As reported recently, LMWH becomes a medium‐potential candidate for treating FGR 5 . One study reported that LMWH does not cross the placenta, indicating that LMWH is a safe therapeutic option for FGR 24 .…”
Section: Discussionmentioning
confidence: 80%
“…So far, there is no effective treatment available for placenta‐mediated FGR, which is an active field for clinical research. As reported recently, LMWH becomes a medium‐potential candidate for treating FGR 5 . One study reported that LMWH does not cross the placenta, indicating that LMWH is a safe therapeutic option for FGR 24 .…”
Section: Discussionmentioning
confidence: 80%
“…The Dutch STRIDER group reported an increased risk of neonatal persistent pulmonary hypertension (PPHN) due to maternal sildenafil administration, which generated global media interest [37]. Based on the above, the benefits of sildenafil for the treatment of FGR are considered negative, and even harmful [11,41]. Subsequent data from neonates born to the Dutch STRIDER participants have been evaluated for causes of PPHN [40].…”
Section: Sildenafilmentioning
confidence: 99%
“…The review determined that tadalafil was safe for pregnant women, fetuses, and neonates. Lim et al described an analysis of new candidates for the prevention and treatment of FGR [11]. Tadalafil was ranked as a "medium-potential" drug for the treatment of FGR.…”
Section: Systematic Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…The early detection of pregnant women at high risk of developing FGR would allow the application of promising treatment strategies to improve fetal growth. Several randomized controlled trials (RCTs) have shown that FGR-specific treatments, such as maternal micronutrient and amino acid supplementation (iron, zinc, calcium, magnesium, N-acetyl cysteine/L-Arginine), maternal nitric oxide supplementation, maternal growth hormone supplementation, aspirin, antiplatelet/anticoagulant agents, calcium channel blockers, proton pump inhibitors, and melatonin/heparin, can improve birth weight in FGR pregnancies [15][16][17][18][19][20][21][22][23][24]. These treatments appear to largely reflect the current understanding of the etiology of this condition.…”
Section: Introductionmentioning
confidence: 99%